IDENTIFIKASI RISIKO RESIDUAL CONTAMINATION AKIBAT KETIDAKEFEKTIFAN TANK CLEANING PADA KAPAL MT. JOY CHEMIST - Delian Alfath, Galih; Wibowo, Wahju; Choeroni, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
On March 23, 2024, MT. Joy Chemist failed a tank inspection at SK Gas 1 Terminal, Ulsan, South Korea, due to residual cargo, delaying loading. This study analyzes tank cleaning for Mineral Base Oil, causes of residual contamination, and strategies for improving tank cleanliness. Data were collected through observations, interviews with the Chief Officer, Boatswain, and AB, and document analysis. Fishbone analysis found suboptimal equipment, weak supervision, and inefficient time allocation as key factors. Recommendations include equipment maintenance, better time management, and strict SOP-based supervision to enhance tank cleaning effectiveness and vessel efficiency.